Employability of HRD graduates : bridging theory to practice through industrial training experience - Hamzah, Siti Raba’ah; Omar, Zoharah; Suandi, Turiman; Ishak, Khairul Anwar (2011)
This study is to determine the extent to which student industrial training helps in increasing students’ employability skills while they were at the agencies. Data were gathered by using questionnaires involving students of the Bachelor of Science (Human Resource Development), UPM. The findings indicated that students were very satisfied with the exposures and experience that they have gained. The main experiences in human resource development are in the management of training programs; working in the personnel section; staff development; and safety and welfare of employees. The experiences acquired, according to the respondents, helped a great deal in getting themselves employed in various government and private agencies.